Psychosocial adjustment during cross-cultural transitions : a case study of foreign students in IIUM - Mohamadou, Galy (International Islamic University Malaysia, 1999)
This research attempts to study some factors related to adjustment of foreign students in the International Islamic University Malaysia. Two hundred and forty six (246) student sojourners from thirty four (34) countries completed a five-page questionnaire that assesses psychological (mood disturbance, depression and the level of general functioning) and sociocultural (social difficulty, and social isolation) aspects of adjustment. These two aspects of adjustment were investigated in relation to the following variables: cultural background (region of origin), knowledge of Bahasa malaysia, interaction with co-nationals or other students, marital status, participation in host social activities, the level of students' commitment to religion and period of stay in Malaysia. Results indicated that cultural background,m knowledge of the language of host country, students' marital status, and interaction with co-nationals or other foreign students, and invoolvement in the host social ativities were significantly related to sojourner adjustment. Knowledge of the language of host country was found to be significantly related with all measures of psychological and sociocultural adjustment. Students from non-ASEAN countries, Middle East, and Eastern Europe were found to be more depressed and had greater sociocultural difficulties than those from ASEAN countries. There was a strong relationship between adjustment outcome and marital status, and length of stay in Malaysia. Religiosity, as measured in this study was not significantly related to adjustment outcome. The study finally discusses the need for developing intervention strategies and for further research in this area.